A comparative study on the mechanical properties of the healthy and varicose human saphenous vein under uniaxial loading. (17th November 2015) - Karimi, Alireza; Navidbakhsh, Mahdi; Kudo, Susumu
Abstract: Saphenous Vein (SV) due to fatness, age, inactiveness, etc. can be afflicted with varicose. The main reason of the varicose vein is believed to be related to the leg muscle pump which is unable to return the blood to the heart in contradiction of the effect of gravity. As a result of the varicose vein, both the structure and mechanical properties of the vein wall would alter. However, so far there is a lack of knowledge on the mechanical properties of the varicose vein. In this study, a comparative study was carried out to measure the elastic and hyperelastic mechanical properties of the healthy and varicose SVs. Healthy and varicose SVs were removed at autopsy and surgery from seven individuals and then axial tensile load was applied to them up to the failure point. In order to investigate the mechanical behaviour of the vein, this study was benefitted from three different stress definitions, such as 2nd Piola-Kichhoff, engineering and true stresses and four different strain definitions, i.e. Almansi-Hamel, Green-St. Venant, engineering and true strains, to determine the linear mechanical properties of the SVs. A Digital Image Correlation (DIC) technique was used to measure the true strain of the vein walls during load bearing. The non-linear mechanical behaviour of the SVs was also computationally evaluated via the Mooney-Rivlin material model. The true/Cauchy stress–strain diagram exhibited the elastic modulus of the varicose SVs as 45.11% lower than that of the healthy ones. Furthermore, by variation of the stress a significant alteration on the maximum stress of the healthy SVs was observed, but then not for the varicose veins. Additionally, the highest stresses of 4.99 and 0.65 MPa were observed for the healthy and varicose SVs, respectively. These results indicate a weakness in the mechanical strength of the SV when it becomes varicose, owing to the degradation of the elastin and collagen content of the SV. The Mooney-Rivlin hyperelastic and the Finite Element (FE) data were finally well compared to the experimental data.